INTEREST-RELATED EDUCATION TEACHER'S ROLE IN VALUES CREATING - Pavlovs, Māris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the past, the professional and private life of the teacher was of equal importance to be a model for the child. Later, these areas were separated, and it was even advisable for the teacher to avoid expressing their values. Adolescents want school to give them understanding of values and relationships. Unlike general education, interest-related education is voluntary. Positive feedback on after-school activities is linked to improvements in school performance. Interest-related education strengthens mental health and the ability to overcome psychological difficulties. Nowadays there are different opinions about where the child's morale develops at home, school or elsewhere. Educational institutions have a close connection with the values of education and teachers have a moral impact on schoolchildren. The paper examines several value-oriented creation methods. The author of the paper carried out a study of interest-related education students about their values and experience in out-of-school activities. It is concluded that interest-related education has no pronounced impact on value orientation.